Exploring youth information-seeking behaviour and mobile technologies through a secondary analysis of qualitative data. (September 2018) - Bowler, Leanne; Julien, Heidi; Haddon, Leslie
This paper examines issues associated with secondary analysis of qualitative data and their implications for information behaviour scholarship. Secondary data analysis poses a range of potential challenges for data creators, but also opportunities, including the ability to expand theory to a wider context, strengthen the reliability and validity of existing theory, gain access to populations that may be difficult to access, and to promote data archiving. The paper uses as a case study of secondary data analysis the results from our re-examination of data gathered previously in the European Union project Net Children Go Mobile, drawing from the interview transcripts from the 34 children in the UK data set. Our approach to secondary analysis was reanalysis, applying a new interpretive lens to the data that necessitated new questions in order to reveal hidden layers in the data. The data was analysed for evidence of information behaviour in order to understand how mobile technologies may be changing the way that young people seek and use information. The reanalysis of the data set supported existing models of information behaviour but revealed new ways of information seeking based on the affordances of screen size and data plans.